ZAKAT MANAGEMENT TO BUILD COMMUNITY WELFARE IN BENGKALIS REGENCY, RIAU PROVINCE - Zulfikar Hasan; Julia Sukma; Kamiluddin Kamiluddin (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This study aims to determine the strategy for managing zakat funds to improve people's welfare at the Bengkalis Regional Zakat Agency (BAZNAS).The research was conducted using a qualitative approach with descriptive methods, in which the data were obtained through interviews, observation, documentation, and a literature review. The results showed that the strategy for managing zakat funds used by the Amil Zakat Agency of Bengkalis Regency was to increase cooperation with various agencies, including government agencies, often by conducting socialization through seminars on zakat. They were growing the competence of Amil Human Resources (HR), the Zakat Collection Unit (UPZ), and volunteers and developing an information and communication technology (ICT) system for managing zakat. While the obstacles are the lack of public understanding of zakat and the lack of public trust in the Amil Zakat Agency, Bengkalis Regency. The solutions implemented by BAZNAS Bengkalis Regency to overcome obstacles include BAZNAS having to carry out transparency in management, modernization of control, and publication of zakat management. The Bengkalis Regency National Amil Zakat Agency (BAZNAS) needs to involve government and private institutions in programs that can assist mustahik in using zakat funds. As well as, the role of local government in improving the management of zakat can increase people's motivation to pay zakat. There needs to be in-depth research on zakat in the regions, and Bengkalis Regency has a different program from the other areas in Indonesia.